Nurturing entrepreneurship and growing entrepreneurs - LIM, Sun Sun (Institutional Knowledge at Singapore Management University, 2024)
How Southeast Asia’s universities can pave the way. Universities in Southeast Asia: 1. Can unlock the potential of changemakers in driving economic growth through entrepreneurship education. 2. Accelerate the growth of the ASEAN start-up ecosystem by facilitating technology commercialisation, leveraging regional networks for mentorship and funding, and fostering cross-border collaborations. 3. Have birthed at least five of Southeast Asia's unicorns and are set to lead the way in producing more.